TEORI INVISIBLE HAND ADAM SMITH DALAM PERSPEKTIF EKONOMI ISLAM - KAH, Rustam Dahar (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2012)
Adam Smith as the founder of modern economics laid the basic foundation for economic development through the capitalist system in which capital factor used as a measuring tool for economic success. One opinion of Adam Smith